Contribuição ao conhecimento da fauna Helmintológica da região Amazônica - Cestódeos On some Cestodes of the Amazon Region - R. Magalhães Pinto; Delir Corrêa Gomes (Memorias do Instituto Oswaldo Cruz, 1976)
Do material proveniente da Região Amazônica, os autores iniciam uma série de publicações, que atualizem o conhecimento de sua fauna helmintológica. Apresentando a parte referente aos Cestódeos, eles redescrevem três espécies: Raillietina (R.) alouattae baylis, 1947, Paronia variabilis (Fuhrmann, 1904), Fuhrmann, 1921 e Anomotaenia brasiliensis (Fuhrmann, 1908) e fazem referência a duas outras: Oochoristica fuhrmanni Hugues, 1940 e Mathevotaenia bivittata (Janicki, 1904). Concerning to the Amazon Region, everything about it arises the greatest interest when one deals with its natural resources. For this reason, the authors, introducing this work, present its first part, which consists of some cestodes recovered from Vertebrates in 1969. So, three species, are redescribed and two only refered. Raillietina (R.) alouattae Baylis, 1947 is marked for the first time in Brazil. The authors ratify the original descriptions of Paronia variabilis (Fuhrmann, 1904) Fuhrmann, 1921 and Anomotaenia brasiliensis Fuhrmann, 1908, presenting original camera lucida drawings in order to accomplish their knowledge. Of Anomotaenia brasiliensis they also rectify the year of its proposition from 1907 to 1908, when the work was printed. Oochoristica fuhrmanni Hugues, 1940 and Mathevotaenia bivittata Janicki, 1904) are only listed for they are well known by now, to justify a revision.